Price Transmission Analysis in Iran Chicken Market - Seyed Safdar Hosseini; Afsaneh Nikoukar; Arash Dourandish (International Journal of Agricultural Management and Development, 2012)
Over the past three decades vertical price transmissionanalysis has been the subject of considerable attention inapplied agricultural economics. It has been argued that theexistence of asymmetric price transmission generates rents formarketing and processing agents. Retail prices allegedly movefaster upwards than downwards in response to farm level pricemovements. This is an important issue for many agriculturalmarkets, including the Iranian chicken market. Chicken is animportant source of nutrition in Iranian society and many ruralhouseholds depend on this commodity market as a source of income.The purpose of this paper is to analyze the extent, if any,of asymmetric price transmission in Iran chicken market usingthe Houck, Error Correction and Threshold models. The analysisis based on weekly chicken price data at farm and retail levelsover the period October 2002 to March 2006. The results oftests on all three models show that price transmission in Iranianchicken market is long-run symmetric, but short-run asymmetric.Increases in the farm price transmit immediately to the retaillevel, while decreases in farm price transmit relatively moreslowly to the retail level. We conjecture the asymmetric pricetransmission in this market is the result of high inflation ratesthat lead the consumers to expect continual price increases anda different adjustment costs in the upwards direction comparedto the downwards direction for the marketing agents and a noncompetitiveslaughtering industry and that looking for ways tomake this sector of the chicken supply chain more competitivewill foster greater price transmission symmetry and lead towelfare gains for both consumers and agricultural producers.